PELIBATAN ORANG TUA DALAM PEMBELAJARAN DI MASA PANDEMI COVID-19 SMK PIRI 1 YOGYAKARTA - Enggar Fata; Kir Haryana (Journal of Automotive Technology and Education, 2024)
This study aims to find out: (1) involvement of parents in learning assistance in the Covid-19 period of SMK PIRI 1 Yogyakarta; (2) constraints for parents in learning assistance in the Covid-19 period of SMK PIRI 1 Yogyakarta. This research uses a type of descriptive research with a quantitative approach. The population used in this study was 20 students, 20 parents, and 16 teachers of class X TBSM. The sample size of the study was 19 students, 5 parents, 5 teachers of class X TBSM 1 according to the sample size of Gay and Diehl. The data is obtained using the following instruments: (1) a closed student questionnaire; (2) open and closed questionnaires of parents; (3) open and closed questionnaires of teachers. The analysis of this research data was done with percentages and descriptive. The results of this study are: (1) The level of involvement of parents in learning assistance during the Covid-19 pandemic of SMK PIRI 1 Yogyakarta is in the high category with a percentage of 93.49%; (2) Parents' constraints in learning assistance during the Covid-19 pandemic are influenced by the following factors: (a) educational background; (b) economic level; (c) types of parental employment; (d) parent's available time.